Troll swap - Hodgkinson, Leigh (Nosy Crow, an imprint of Candlewick Press, 2014)
Timothy Limpet feels out of place in the troll family - he likes things to be just so, and most trolls, frankly, don't. Tabitha Lumpit likes things to be loud, loopy and messy and she feels a fish out of water in her very neat family.